Gratifikasi Seksual sebagai Bentuk Tindak Pidana Korupsi: Analisis Yuridis Berdasarkan Undang-Undang Nomor 20 Tahun 2001 dan Prinsip Hukum Islam - Andi Rachmat Indra; Ruslan Abdul Gani; Rahmi Hidayati; Abdul Halim (Desentralisasi : Jurnal Hukum, Kebijakan Publik, dan Pemerintahan, 2026)
From the perspective of criminal liability theory, criminal policy, and Islamic law, sexual gratification is a form of corruption. According to positive criminal law, a person can only be held liable when three essential elements are fulfilled: an unlawful act, culpability (dolus or culpa), and the capacity for responsibility. However, in the context of public office, sexual gratification constitutes an unlawful act because it involves the acceptance of non-fina. Since the acceptance of sexual services within a power relationship usually indicates awareness of reciprocal policy gains, purpose (dolus) is frequently dominating. From the perspective of criminal policy, the restriction of sexual gratification reflects the growth of corruption as a white collar crime—a term coined by Edwin H. Sutherland—where abuse of power encompasses intangible rewards in addition to monetary transfers. According to Islamic law, sexual enjoyment constitutes two violations: it may be considered risywah (bribery) because of its transactional motive, and it may also be considered jarimah zina if it takes place outside of a legally recognized marriage. Such behaviors compromise the protection of property, ancestry, and religion through the framework of maqāṣid al-sharī‘ah developed by Abu Ishaq al-Shatibi in Al-Muwafaqat. The study comes to the conclusion that in order to guarantee accountability, protect public integrity, and promote social welfare, it is imperative to develop legal interpretation and evidential procedures.